The relationship between exchange rate, unemployment and inflation in South Africa - Semosa, Phetole Donald (My University, 2017)
The relationship between unemployment, exchange rate and inflation has been a subject of debate for many years. Given the fact that South Africa is faced with a very low economic growth rate, inflation rate which is likely to go beyond the upper band of 6 percent and a high level of unemployment, policy makers are often faced with the trade-off between unemployment and inflation rate in the country. The purpose of this study is to determine the relationship between exchange rate, unemployment and inflation in South Africa. The study employed Johansen cointegration procedures and the vector error correction model (VECM) to capture the relationship between the variables. The Engle-Granger causality test was also employed to analyse causality amongst the variables. The results of Johansen cointegration test indicate that there is a long-run equilibrium relationship between the variables. The VECM also confirmed the existence of short-run equilibrium relationship between the variables. The nature of the relationship indicates that there is a significant negative relationship between unemployment and inflation in South Africa. This implies that policy makers are been faced with the trade-off between these two variables. The results further indicate that inflation is positively related to exchange rate, meaning a depreciation of the Rand (South African currency) in the foreign exchange market will feed to inflation in the home country. Furthermore, it is also indicated that unemployment is positively related to exchange rate. Meaning, a depreciation of the Rand in the foreign exchange market increases the level of unemployment in South Africa. All the results appeared to be significant. Policies aimed at lowering unemployment and inflation rate are recommended. It is also recommended that policy makers in South Africa take measures to improve the quality of education, skills training and steps to increase the labour intensity of production.
Thesis (M. Com.(Economics)) -- University of Limpopo, 2017
Keywords: Exchange rates; Inflation rate; Unemployment; Vector Error Correction Model (VECM); Johansen cointegration and Augmented Dickey-Fuller test (ADF); JEL Classification: B22, B23, E03, E10, F31 and F62; Foreign exchange rates -- South Africa; Inflation (Finance); Employment stabilization